The Incidence of Depression in Patients With Diabetic Foot Ulcers: A Systematic Review and Meta-Analysis. (June 2022) - Jiang, Fu-Hui; Liu, Xiao-Man; Yu, Hai-Rong; Qian, Yan; Chen, Hong-Lin
Some patients with diabetic foot ulcers (DFUs) may suffer from depression, but the latest information regarding the incidence of depression in patients with DFUs is limited. This review aimed to provide up-to-date information concerning the incidence of depression in patients with DFUs. We searched the literature in PubMed and Web of Science databases, limited to English publications. 11 eligible studies with a total of 2117 participants were included in this review. A random-effects model was applied due to high heterogeneity. The incidence of depression in patients with DFUs ranged from 26% (95% confidence interval [CI] = 19% to 33%) to 85% (95% CI = 78% to 92%), and was 47% (95% CI = 36% to 58%) after systematically summarizing. Subgroup analyses suggested that the incidence of depression were 49% (95%CI = 35% to 63%) in Europe, 37% (95% CI = 23% to 51%) in Asia, 62% (95% CI = 48% to 76%) in North America. Additionally, the incidence of depression were 40% (95% CI = 29% to 50%) in prospective studies, 55% (95% CI = 28% to 82%) in retrospective studies, 40% (95% CI = 29% to 50%) in cross-sectional studies. Furthermore, the incidence of depression were 43% (95% CI = 25% to 60%), 49% (95% CI = 35% to 63%), 68% (95% CI = 35% to 102%), 32% (95% CI = 26% to 38%), and 28% (95% CI = 18% to 38%) in patients with DFUs assessed by the Hospital Anxiety and Depression Scale, EuroQol 5-Dimension Questionnaire, Geriatric Depression Scale, Diagnostic and Statistical Manual of Mental Disorders, 4th edition, and the Center for Epidemiologic Studies Depression Scale, respectively. The estimates were robust in the sensitivity analysis. According to the meta-regression analyses, diabetes mellitus duration ( t = 0.93, P = .422), publication years ( t = −0.72, P = .488), and age of subjects ( t = 0.01, P = .989) were not the sources of high heterogeneity. Our meta-analysis showed nearly half of patients with DFUs had depression problems.